2021
DOI: 10.3390/children8111072
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Incidence of Pediatric Intussusception during COVID-19

Abstract: Coronavirus disease 2019 (COVID-19) changed the epidemiology of various diseases. The present study retrospectively investigates the epidemiologic and clinical changes in pediatric intussusception for ages ≤ 7 years before (February 2019–January 2020) and after (February 2020–January 2021) the COVID-19 outbreak in a single pediatric emergency department of a university-affiliated tertiary hospital. The incidence of communicable diseases—defined as infectious diseases with the potential for human-to-human trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 39 publications
(53 reference statements)
2
9
0
1
Order By: Relevance
“…As infection prevention practices are emphasized and recommended during the COVID-19 pandemic, it could be presumed that the incidence of intussusception has also decreased because other viral infections in children have decreased. This interpretation is supported by a study by Park et al, who reported that a decrease in ED visits for communicable diseases was more pronounced than a decrease in visits for noncommunicable diseases, and the former was significantly correlated with the decrease in visits of intussusception [ 13 ]. Children with intussusception may not have visited the ED because their parents were reluctant to visit the hospital.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…As infection prevention practices are emphasized and recommended during the COVID-19 pandemic, it could be presumed that the incidence of intussusception has also decreased because other viral infections in children have decreased. This interpretation is supported by a study by Park et al, who reported that a decrease in ED visits for communicable diseases was more pronounced than a decrease in visits for noncommunicable diseases, and the former was significantly correlated with the decrease in visits of intussusception [ 13 ]. Children with intussusception may not have visited the ED because their parents were reluctant to visit the hospital.…”
Section: Discussionmentioning
confidence: 52%
“…On the other hand, there have been few reports of intussusceptions in pediatric patients. In a study using data from one pediatric emergency center in Korea, it was reported that the number of intussusception patients visiting the emergency department decreased at the same time as infectious diseases after the COVID-19 epidemic [ 13 ]. In most cases, the cause of intussusception in children is idiopathic; however, it may be caused by lymphoid hyperplasia due to a viral infection [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al ( 29 ) reported that a history of infection was significantly more common in non-recurrent (72/114, 63.2%) than recurrent (5/23, 21.7%) intussusceptions ( P < 0.001). Park et al ( 30 ) found that the incidence of pediatric intussusceptions decreased after the COVID-19 pandemic. That decreased incidence may be related to the reduced circulation of communicable diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Die Inzidenz pädiatrischer Invaginationen scheint während der COVID-19(„coronavirus disease 2019“)-Pandemie eher abgenommen zu haben [ 1 ]. Nichtdestotrotz mehren sich Berichte einzelner SARS-CoV-2-assoziierter Invaginationen weltweit.…”
Section: Sars-cov-2-assoziierte Ileokolische Invaginationunclassified